Численно-полевой анализ режимов возбуждения и разных видов реакции якоря в мощном турбогенераторе - Милых, Владимир Иванович; Полякова, Наталия Владимировна; Milykh, V. I.; Polyakova, N. V. (Запорожский национальный технический университет, 2013)
Представлены принцип и результаты численно-полевого анализа разных режимов возбуждения и видов реакции якоря турбогенератора. Показаны выбор факторов возбуждения магнитного поля и метод определения на его основе магнитного потокосцепления, ЭДС и фазовых соотношений между ними и токами. Представлены картины магнитных полей во всех режимах, а также дан принцип построения соответствующих векторных диаграмм. Проведенные исследования могут быть основой совершенствования проектирования турбогенераторов и других электрических машин.

Principle and the results numerical field analysis of the different excitation modes and of the different types of the armature reaction of powerful turbogenerator are presented. A selection of the factors of the magnetic field excitation in the idle mode, the rated load and short-circuit, as well as those specific modes that are characterized by longitudinal demagnetizing and magnetizing and more cross-reaction of the armature excitation of the magnetic field only the stator winding along the longitudinal and transverse axes of the rotor is shown. The principle, which allows by the results of the calculation of the magnetic field in each mode to determine the key electromagnetic values (magnetic flux and EMF) and the phase relationship between them and the currents is considered. The pictures of the magnetic fields are graphically presented in all modes, and also principle of construction of the corresponding vector diagrams is presented on the basis of calculation of these fields. In the original received vector diagrams it is possible to qualitatively and quantitatively identify the share and role of the magnetic field of the rotor and the stator magnetic field. The conducted research can be the basis for improving the system of study, analysis and design of turbogenerators and other electric machines because the considered method of analysis of magnetic fields is quite universal
The numerical field analysis of excitation modes and of the different types of the armature reaction in a powerful turbogenerator
Keywords: магнитные поля; режимы возбуждения; векторные диаграммы; magnetic fields; modes of excitation; vector diagrams